Respuesta :

(3,-1).  You can know the answer by plugging in the x and y values into the equations and it is a solution if both are true.

Answer: (3,-1)

Step-by-step explanation:  y=3x-10 and 2x+3y=3    

                    putting y=3x-10 in 2x+3y=3

           ⇒      2x+3(3x-10)=3

           ⇒      2x+9x-30=3

           ⇒      11x=33

           ⇒       x=33/11

           ⇒       x=3

Putting x=3 in y=3x-10 ,we get

                           y=3×3-10

                       ⇒    y=9-10

                       ⇒    y=-1